Ethics in qualitative research : controversies and contexts - Hammersley, Martyn (SAGE, 2016)
This volume explores the field of research ethics and presents a distinctive perspective; one that is at odds with the assumptions underpinning ethical regulation, but also with the views of many qualitative researchers today.